Pengaruh Air Lindi Sampah Pasar Dan Lumpur Tinja Kota Palangka Raya Terhadap Pertumbuhan Dan Hasil Tanaman Kailan (Brassica oleraceae, L.) di Lahan Gambut Pedalaman - Ruben Tinting S; Titin Apung Atika; Oesin Oemar; Susi Kresnatita; Suparno Suparno; Moch Anwar; Bakti Panjaitan (JURNAL AGRIMENT, 2023)
This study was aimed to ascertain how leachate and faecal sludge interacted to affect kailan plant development and yield in inland peat soil. The design used was Factorial Randomised Complete Block Design with 2 factors. The first factor was leachate water consisting of 4 levels, namely L0 (0 mL), L1(150 mL), L2(250 mL), and L3(350 mL), and the second factor was sewage sludge consisting of 4 levels, namely T0 (0 gr), T1(100 gr), T2(200 gr), and T3(400 gr). The results showed that there was a very significant interaction between the application of leachate water and faecal sludge on plant height, leaf area, and fresh weight of plants but there was no interaction between the application of leachate water and faecal sludge on the number of leaves and fresh weight of roots. The optimal interaction of leachate and faecal sludge doses on the growth and yield of kailan plants is in the treatment of leachate at a doses of 150 mL/polybag and faecal sludge at a doses of 200 gr/polybag.